Master decomposition curve of carbonaceous materials used in casting powders - Benavidez, E. (2017)
Casting powders are used in the continuous casting process of steels. These powders contain several oxides, fluoride compounds and carbonaceous materials. The decomposition kinetics of these carbonaceous materials regulates the melting rate of casting powders. In a previous work, a decomposition kinetics of two carbonaceous materials (coke and graphite) added to a casting powder was studied. Based on those data, in the present work, master decomposition curves (MDC) of these powders were constructed. For this, the values of both the activation energy (E) and the degree of decomposition (α), obtained in the thermogravimetric tests, were used for each heating rate (β). Then, the work of decomposition (θD) was calculated and the MDC was obtained. From the MDC, it was possible to predict the time (t) needed to produce a given degree of decomposition (α) at different temperatures (T). Taking this into account, it was possible to validate the master decomposition curves through different thermal treatments, where the degree of decomposition was calculated by interpolating the MDCs. These values were compared with those determined experimentally by measuring the mass loss in each heat treatment. In all cases, the results showed a good correlation between the predicted and measured values. It is concluded that the use of the MDC represents a useful tool to evaluate and compare the behavior of carbonaceous materials added to casting powder.